2008
DOI: 10.1163/156856208786052407
|View full text |Cite
|
Sign up to set email alerts
|

Modulus-dependent macrophage adhesion and behavior

Abstract: Macrophage attachment and activation to implanted materials is crucial in determining the extent of acute and chronic inflammation, and biomaterials degradation. In an effort to improve implant performance, considerable attention has centered on altering material surface chemistry to modulate macrophage behavior. In this work, the influence of the modulus of a material on the behavior of model macrophages (i.e., human promonocytic THP-1 cells) was investigated. We synthesized interpenetrating polymer network (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 33 publications
4
77
0
Order By: Relevance
“…For example, it has been shown that cellular behavior is influenced by the compliance of the substrate on which the cell resides. 15,16,18,20,23,29,[96][97][98][99][100][101] To accurately relate these laboratory observations back to in vivo cell function, compliance of the tissue and the matrix with which a cell interacts must be characterized. These values can be obtained with the AFM or The values are the averages without the suspected outliers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that cellular behavior is influenced by the compliance of the substrate on which the cell resides. 15,16,18,20,23,29,[96][97][98][99][100][101] To accurately relate these laboratory observations back to in vivo cell function, compliance of the tissue and the matrix with which a cell interacts must be characterized. These values can be obtained with the AFM or The values are the averages without the suspected outliers.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the rather low E-moduli of the materials (10e60 kPa), as earlier studies showed increasing macrophage attachment to materials with increasing Young's modulus, preferentially > 100 kPa [37]. Additionally, highly hydrophilic materials (like gelatin-based hydrogels) tend to show low macrophage adhesion [38].…”
Section: Reaction Of Macrophages and Granulocytesmentioning
confidence: 93%
“…[46][47][48] Specifically, soft substrates tend to inhibit cell spreading and slow migration compared to their stiffer counterparts 49,50 ; they also induce differentiation of mesenchymal stem cells to specific phenotypes. 51 In this study, a mechanical influence could explain both the delayed proliferation and slower overall rates of proliferation for cells cultured on edsIPN compared with TCPS.…”
Section: Discussionmentioning
confidence: 99%